1992
DOI: 10.1001/jama.1992.03480070057030
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Benign Breast Disease and the Risk of Breast Cancer

Abstract: These results confirm the marked increase in breast cancer risk among women with atypical hyperplasia, particularly in premenopausal women, and suggest that these women should be encouraged to undergo frequent breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(82 citation statements)
references
References 9 publications
7
72
1
2
Order By: Relevance
“…9,10,24–26 In addition, over-interpretation of atypia in a biopsy with otherwise benign findings can result in unnecessary heightened surveillance, clinical intervention, costs, and anxiety. 2730 It has been recently suggested that women with a diagnosis of atypia on a breast biopsy consider annual screening magnetic resonance imaging examinations and chemoprevention. 31 Given our findings, clinicians and patients may want to obtain a formal second opinion for breast atypia prior to initiating more intensive surveillance or risk reduction using chemo-prevention or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,24–26 In addition, over-interpretation of atypia in a biopsy with otherwise benign findings can result in unnecessary heightened surveillance, clinical intervention, costs, and anxiety. 2730 It has been recently suggested that women with a diagnosis of atypia on a breast biopsy consider annual screening magnetic resonance imaging examinations and chemoprevention. 31 Given our findings, clinicians and patients may want to obtain a formal second opinion for breast atypia prior to initiating more intensive surveillance or risk reduction using chemo-prevention or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Benign breast disease (BBD) confers an increased risk of breast cancer and may represent an earlier stage of breast carcinogenesis. BBD is a heterogeneous condition with several histologic subtypes; research has consistently found that proliferative BBD without atypia moderately increases risk of breast cancer later in life (1.3–1.9 fold), while proliferative BBD with atypical hyperplasia confers between 4 and 13-fold increased risk of breast cancer [8, 11, 12, 22, 35]. …”
Section: Introductionmentioning
confidence: 99%
“…Proliferative benign breast disease increases a woman’s risk of breast cancer [3] and efforts to reduce the occurrence of proliferative BBD are likely to augment cancer prevention efforts. Reflecting the complex multiple step process of genetic alteration for development of human cancers, long time periods are required for tumor progression to accumulate[4].…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Compared with non-proliferative BBD (which does not appear to increase the risk of breast cancer [28]), the relative risk of subsequent breast cancer is 1.3-1.9 for proliferative BBD without atypia and 4.1-5.3 for proliferative BBD with atypia. [29,26,30,3] Proliferative BBD is thus a well-confirmed risk marker of breast cancer risk, and may in some cases be a precursor of breast cancer [31]. See Figure 1 for a morphological model of breast cancer development.…”
Section: Introductionmentioning
confidence: 99%